2014
DOI: 10.1089/thy.2013.0191
|View full text |Cite
|
Sign up to set email alerts
|

Serum Thyroglobulin Improves the Sensitivity of the McGill Thyroid Nodule Score for Well-Differentiated Thyroid Cancer

Abstract: This study shows that adding Tg to the MTNS increases the sensitivity of this scoring system. Moreover, it suggests that a combined scoring system such as the MTNS+ can accurately stratify the risk of well-differentiated malignancy in patients with thyroid nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…They have concluded that patients with MNG and "negative" FNAB results but with high 18F-FDG uptake in the thyroid gland require a particularly careful diagnosis and radical treatment by total or near total strumectomy. Further, determination of the Tg level, along with the McGill Thyroid Nodule Score (MTNS), increase the sensitivity of detection of well-differentiated malignancy in patients with thyroid nodules (MNG) [62]. …”
Section: Discussionmentioning
confidence: 99%
“…They have concluded that patients with MNG and "negative" FNAB results but with high 18F-FDG uptake in the thyroid gland require a particularly careful diagnosis and radical treatment by total or near total strumectomy. Further, determination of the Tg level, along with the McGill Thyroid Nodule Score (MTNS), increase the sensitivity of detection of well-differentiated malignancy in patients with thyroid nodules (MNG) [62]. …”
Section: Discussionmentioning
confidence: 99%
“…Preoperative thyroglobulin measurement is considered to have limited value, although a number of studies report that an elevated preoperative serum thyroglobulin is a risk factor for nodular malignancy [8487]. In addition, the relationship between the preoperative serum thyroglobulin and tumor burden may give some indication of the tumor's efficiency for thyroglobulin secretion and set a threshold for determining the significance of postoperative serum thyroglobulin changes [2].…”
Section: Postoperative Serum Thyroglobulin Monitoringmentioning
confidence: 99%
“…Previous reports have shown a relationship between elevated measurements of Tg and well-differentiated thyroid carcinoma (WDTC). Tg has been recognized as an established tumor marker for thyroid cancer [6][7][8][9]. However, serum thyroglobulin antibody (TgAb) levels may interact with Tg and give a lower serum Tg value.…”
Section: Introductionmentioning
confidence: 99%